α-MoO3 Micro- and Nanoparticles as Catalysts for Biofuel Production - Silva Lucena de Medeiros, Suelen Alves; Menezes de Oliveira, André Luiz; Duarte, Thiago Marinho; Kennedy, Brendan James; Rostas, Arpad Mihai; Negrila, Constantin Catalin; Galca, Aurelian Catalin; da Silva Maia, Ary; Sambrano, Julio Ricardo [UNESP]; Dantas, Marta Célia; Felix Farias, Ana Flávia; Garcia dos Santos, Iêda Maria (American Chemical Society (ACS), 2024)
Herein, α-MoO3 micro- and nanoparticles were synthesized by a modified Pechini method, and the impact of the crystal structure and crystal growth orientation on the formation of ionic defects and, consequently, on the catalytic performance of the materials in the ethylic transesterification reaction for biodiesel production was investigated. Structural refinements from X-ray diffraction data and Raman spectra revealed the formation of α-MoO3 in a Pbnm orthorhombic phase, with nanoplate-like morphology at 500 °C (thickness between 100 and 260 nm) or ribbon-like morphology at 700 °C (thickness between 400 and 900 nm). An anisotropic crystal orientation along the [010] direction was observed with an increase of the calcination temperature. We emphasize the dependence of the orientation change with the elimination of ionic-type defects (oxygen vacancies and reduced Mo5+ centers) by the temperature using complementary techniques such as X-ray photoelectron and electron paramagnetic resonance spectroscopies. The catalytic activity of the samples depends on the orientation process and the presence of defects that act as acid-active sites on the catalyst surface and therefore play an important role in biodiesel production. This effect was confirmed by surface stability and reactivity simulated by density functional theory calculations, suggesting that the Mo and O surface terminals greatly impacted the interface catalytic reaction. The highest catalytic performance toward the biodiesel conversion (89% of conversion at 150 °C for 2 h) was achieved for the polycrystalline catalyst calcined at 500 °C, which was correlated with random crystal orientation and the presence of reduced Mo5+ and oxygen vacancy centers on the different facets exposed on the surface. The biodiesel production was confirmed by 1H and 13C NMR spectroscopy and gas chromatography analysis.
Keywords: acidity; crystal orientation; DFT simulations; ionic defects; molybdenum oxide; transesterification reaction